The Effect of Using Interactive English Language E-Book for the Fourth Graders' Listening and Reading Skills and Their Reflective Thinking at Martyr Yasseir Arafat Secondary School - Rjoob, Mohammad Mahmoud (Journal of Curriculum and Teaching Methodology, 2023)
This study investigated the effect of using interactive English Language e-book for the fourth graders' listening and reading skills and their reflective thinking at Martyr Yasseir Arafat Secondary School. The study followed an action research method (quantitative and qualitative) because it's practical and relevant form to the classroom research, The participants of this study consisted of 26 male graders for fourth grade at Martyr Yasseir Arafat Secondary in south Hebron district during the second semester 2017/ 2018. This study used three data collection tools including listening, reading test and reflective thinking questionnaire and interview, The collected data was analyzed. The findings of the study reveals that there is a difference of the results between pre listening and reading test and post listening and reading test and there is a positive effect of using interactive English Language e book. Moreover, the result of the reflective questionnaire shows that there are distinct differences between the results in the pre and post reflective thinking questionnaire which indicates there is effect of using interactive English Language e book. Also, the result of the interview reveals that the most of interviewees are motivated in using technology.The researcher recommended to train teachers at in-service on designing, producing and employing e- interactive book in the educational process due to its great benefits and achievable results.
Keywords: interactive e-book; fourth graders; listening skills; reading skills; reflective thinking